The Impact of Aging on Regulatory T-Cells - Fessler, Johannes; Felber, Anja; Duftner, Christina; Dejaco, Christian (Frontiers in Immunology, 2013)
Age related deviations of the immune system contribute to a higher likelihood of infections, cancer and autoimmunity in the elderly. Senescence of T-lymphocytes is characterized by phenotypical and functional changes including the loss of characteristic T-cell surface markers, while an increase of stimulatory receptors, cytotoxicity as well as resistance against apoptosis is observed. One of the key mediators of immune regulation are naturally occurring regulatory T-cells (Tregs). Tregs express high levels of CD25 and the intracellular protein forkhead box P3 (FOXP3); they exert their suppressive functions in contact-dependent as well as contact-independent manners. Quantitative and qualitative defects of Tregs were observed in patients with autoimmune diseases. Increased Treg activity was shown to suppress anti-tumor and anti-infection immunity. The effect of aging on Tregs, and the possible contribution of age-related changes of the Treg pool to the pathophysiology of diseases in the elderly are still poorly understood. Treg homeostasis depends on an intact thymic function and current data suggest that conversion of non-regulatory T-cells into Tregs as well as peripheral expansion of existing Tregs compensates for thymic involution after puberty to maintain constant Treg numbers. In the conventional T-cell subset, peripheral proliferation of T-cells is associated with replicative senescence leading to phenotypical and functional changes. For Tregs, different developmental stages were also described; however, replicative senescence of Tregs has not been observed yet.